Pengaruh Kompetensi Auditor terhadap Pengendalian Internal pada Bank Perekonomian Rakyat: Bukti Empiris dari PT BPR Bank Karanganyar - Dwi Nurma Fitriyani; Ety Meikhati; Erna Chotidjah Suhatmi (Jurnal Ekonomi Bisnis dan Akuntansi, 2026)
This study aims to analyze the effect of auditor competence on internal control in rural banks with a case study at PT BPR Bank Karanganyar. This research employs a quantitative approach with a survey method through questionnaire distribution to 30 respondents selected purposively from internal auditors and related parties. Data were analyzed using validity and reliability tests, as well as simple linear regression analysis with the assistance of SPSS application. The regression results indicate that auditor competence has a positive and significant effect on internal control, as evidenced by the positive regression coefficient value, the t-count value which is greater than the t-table, and the significance level below 0.05. Auditor competence also provides a substantial contribution in explaining the variation of internal control, while the remaining is influenced by other factors outside the research model. These findings indicate that enhancing internal auditor competence is a strategic step for rural banks to strengthen internal control systems and support compliance with applicable regulations.